DETERMINANTS OF THE INCIDENCE OF LOW BIRTH WEIGHT IN SMALL FOR GESTATIONAL AGE (SGA) AND APPROPRIATE GESTATIONAL AGE (AGA) IN RSUD Dr. M YUNUS BENGKULU - Nispi Yulyana; Rialike Burhan; Elvi Destariyani; Rolita Efriani; Iis Mulyati (Poltekkes Kemenkes Bengkulu, 2022)
Low Birth Weight (LBW) is a baby weighing less than 2500 grams regardless of gestational age. The causative factors for the incidence of LBW include small for gestational age (SGA), appropriate gestational age (AGA), and both. This study aimed to determine the determinants of LBW IN SGA and AGA incidence. This observational study uses secondary data with a case-control design. The population in this study were all newborns recorded in the register of the Perinatology Room at RSUD Dr. M. Yunus Bengkulu in 2020-2021, with a total population of 577. The case sample was 223 (SGA = 63 and AGA = 160), taken by total sampling and the control group with a comparison of 1:1 for SGA and AGA. The analysis used univariate, bivariate using chi-square, and multivariate with multiple logistic regression. The results showed that preeclampsia, gemelli, and PROM were significantly related to the incidence of LBW in SGA with p-value <0.05. Maternal age, preeclampsia, and PROM were significantly associated with the incidence of LBW in AGA with p <0.05. The most influential factor in the incidence of LBW in SGA was gemelli (OR=10,759), and the most effective on the incidence of LBW in AGA was preeclampsia (OR=2,476). It is hoped that the hospital can improve its capabilities, skills, and infrastructure to handle maternal and neonatal emergencies through training and seminar.